Ownership-Retention and The Value of Indonesian Initial Public Offering (IPO) Firms in 2013-2016 - Ernie Hendrawaty; Syifa Fadiah Adlina (AFEBI Management and Business Review, 2021)
The study investigates information asymmetry between security issuers and other market participants. Investors and entrepreneurs require reliable information about the firms. Therefore, it is crucial to examine how the top management information can be communicated to other market participants. The empirical implications of the model are tested on the set of 28 of 89 Indonesian firms that made an initial public offering in 2013-2016. The asymmetry problem is most significant when a firm makes a first public issue. Furthermore, the study explains the number of shares retained by the entrepreneur as a signal of IPO firm value.  The test results are generally consistent with the signaling model's predictions, while the role of the controlling variables does not support the firm value.Keywords: Ownership-Retention, Firm Value, Initial Public Offering, IPO